The Current Research of Pesantren Muhammadiyah in Indonesia: A Bibliometric Study from 2011-2020 - Naufal Ahmad Rijalul Alam; Asyraf Isyraqi Jamil; Mohamad Azrien Mohamed Adnan (al-Afkar, Journal For Islamic Studies, 2022)
The number of pesantren Muhammadiyah has increased dramatically in recent years. Therefore, a mapping of pesantren Muhammadiyah research is required to find the trend of publications, article citations, publishers, and keywords. Through bibliometric studies, this article seeks to identify and analyze pesantren Muhammadiyah's studies published in reputable journals between 2011 and 2020. The mind-mapping method used in this study consisted of four stages: first, searching articles from the Google Scholar database using the Publish or Perish (PoP) applications. Second, papers are filtered. Third, double-check and complete the paper metadata. Fourth, arranging bibliometric analysis using the VOSviewer. The investigation yielded four conclusions: first, Pesantren Muhammadiyah publication trends yearly. The study revealed an improving publication trend; second, the scope of religious awareness received the most citations in pesantren Muhammadiyah articles; third, the most reports on pesantren Muhammadiyah and its publisher. The most frequently cited journal is Jurnal Tarbiyatuna, the most commonly cited publisher is Universitas Muhammadiyah Makassar, and the most frequently cited author keywords in pesantren Muhammadiyah articles are Universitas Muhammadiyah Makassar. The most widely used keyword term by authors is pesantren Muhammadiyah. The findings of this study, the number of publications in pesantren Muhammadiyah increased, and the number of citations decreased.